DETERMINAN FIRM VALUE PERUSAHAAN PROPERTY DAN REAL ESTATE - Novan Kurniawan; Marhamah - Marhamah; Jefri Heridiansyah (JURNAL STIE SEMARANG, 2023)
Abstract. Firm Value is an investor's perception of a company's level of success which is often linked to share prices. Firm value is investors' perception of a company which is reflected in its stable share price in the long term. Firm value is proxied by Price Book Value (PBV), which is the comparison between the share price and the book value per share. This research aims to examine the effect of profitability on firm value in property and real estate companies listed on the Indonesia Stock Exchange in 2020-2022. The population in this research is 81 property and real estate companies listed on the Indonesia Stock Exchange (BEI) in 2020-2022. The sample in this study used the Purposive Sampling method so that a sample of 15 issuers was obtained. The variables in this research are Profitability, Leverage, Debt Policy, Liquidity, and Firm Value. The analytical method used in this research is multiple linear regression analysis. Based on the results of data analysis, it is concluded that the profitability variable has no significant effect on Firm Value, the leverage variable has no significant effect on Firm Value, the debt policy variable has no significant effect on Firm Value, the liquidity variable has a significant effect on Firm Value. For investors and potential investors, to look more carefully at market conditions and examine more closely the financial reports submitted by issuers (companies) before making investments, especially in relation to the amount of debt, in making debt policies, companies must pay more attention to liquidity and business risk factors.